Hsa_circ_0010220 regulates miR-198/Syntaxin 6 axis to promote osteosarcoma progression - Lu, Zhaoan (J Bone Oncol, 2021)
BACKGROUND: Circular RNAs (circRNAs) are a class of endogenous RNAs that are involved in osteosarcoma progression. Hsa_circ_0010220 (circ_0010220) is a circRNA generated by gene Rho Guanine Nucleotide Exchange Factor 10 Like (ARHGEF10L) and is upregulated in osteosarcoma, but its functional role in osteosarcoma is limited studied. This study aimed to illustrate the regulatory mechanism underlying circ_0010220 in osteosarcoma. METHODS: 51 paired tumor and normal tissues were obtained from osteosarcoma patients. circ_0010220, microRNA (miR)-198 and Syntaxin 6 (STX6) abundances were examined by quantitative reverse transcription polymerase chain reaction and western blot. Cell proliferation, cell cycle, apoptosis, migration and invasion were analyzed via Cell Counting Kits-8 (CCK-8), colony formation, flow cytometry and transwell analyses. Target relationship was verified via dual-luciferase reporter analysis, RNA immunoprecipitation and pull-down. The in vivo function was analyzed using a xenograft model. RESULTS: Circ_0010220 was elevated in osteosarcoma tissues and cells, and was related to the lower survival rate of osteosarcoma patients. Circ_0010220 knockdown inhibited cell proliferation, migration and invasion, but induced cell cycle arrest and apoptosis in vitro. Besides, circ_0010220 silence curbed the growth of xenograft osteosarcoma tumors in vivo. Mechanistic research revealed that miR-198 is a target of circ_0010220, and directly targets STX6. Moreover, circ_0010220 upregulated the expression of STX6 by sponging miR-198 to regulate cell proliferation, migration, invasion, cell cycle, and apoptosis. CONCLUSION: Circ_0010220 contributes to osteosarcoma progression through mediating miR-198/STX6 axis, which might be a novel therapeutic target for osteosarcoma therapy.